The Prevalence of Academic Procrastination among Students at Medicine Faculty Mulawarman University - Deenadearlova Putri Daryani; Eka Yuni Nugrahayu; Sulistiawati Sulistiawati (Universitas Muhammadiyah Kalimantan Timur, 2021)
Academic procrastination is an act of intentionally postponing completion of assignments and can prevent individuals from starting of finishing assignments. This study aims to describe the prevalence of academic procrastination among students at Medicine Faculty, Mulawarman University. This is a descriptive observational study and the respondents were selected through purposive sampling technique. There were 216 students of 2018, 2019, and 2020 Academic Year at Medicine Faculty selected as the respondents. The primary data were obtained from the questionnaire. The findings revealed that academic procrastination occured to 55.1% respondents more than the average.